PELATIHAN TEKNIK PEMASARAN USAHA EKONOMI KREATIF (UEP) PADA KARANG TARUNA KELURAHAN MARGA MULYA KOTA BEKASI JAWA BARAT DENGAN KEKUATAN PUBLIC RELATIONS - TABRANI SJAFRIZAL; DWINARKO; METHA MADONNA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
One of the activities of the youth organization is to provide businesses with residents who have less or no income. This activity is called Productive Economic Enterprises (UEP). The purpose of forming UEP by members of the youth organization cannot be separated from the desire to make the community prosperous. In this case in the economic or material field. At UED, residents will be guided in carrying out various activities that can support their economic activities. Creating jobs with various businesses. In this UEP, the skills of the members are adjusted, so the expertise they have will be used as a business in a productive economic life. Related to the Productive Economic Enterprises (UEP) formed by members of the youth organization, it should also be noted that UEP inevitably has to adapt to the era of information technology. In the current era of information technology, there is a flood of information, as a result of which people become increasingly critical thinking and skeptical of the superior quality, benefits, of the products they are going to buy. This problem encourages marketing practitioners to take advantage of the power of public relations in their marketing techniques, which in many circumstances are indeed an essential element of any marketing activity.